Effect of chitosan as a functionalization agent on the performance and separation properties of polyimide/multi-walled carbon nanotubes mixed matrix flat sheet membranes - Aroon, Mohammad Ali (Elsevier, 2010)
The effect of chitosan as a functionalization agent on the performance and separation properties of polyimide/multi-walled carbon nanotubes mixed matrix flat sheet membranes were investigated. Polyimide (PI)/raw multi-walled carbon nanotubes (r-MWCNTs) and polyimide (PI)/chitosan-functionalized multi-walled carbon nanotubes (C-f-MWCNTs) mixed matrix membranes were fabricated by phase inversion method. Raw and functionalized multi-walled carbon nanotubes were characterized by transmission electron microscope (TEM). The membrane samples were characterized by SEM, FESEM, DSC and gas permeation tests using He, CO2 and CH4 as test gases. TEM results and gas permeation test using He as test gas showed that r-MWCNTs were generally closed ended and after functionalization, well dispersed open ended chitosan-wrapped MWCNTs were obtained. Gas permeation results showed that addition of 1wt.% (solid base) C-f-MWCNTs into casting dope can increase the CO2 and CH4 permeabilities by 20.48 and 0.71Barrer, respectively. The increase in permeabilities of CO2, CH4 and He in this study can be attributed to the presence of high diffusivity tunnels in the MWCNTs within the polyimide matrix. It is interesting that the CO2/CH4 selectivity was also increased by 51.4% (from 10.9 to 16.5) by addition of C-f-MWCNTs. DSC and FESEM results also revealed a very good dispersion and adhesion of the C-f-MWCNTs in the polyimide matrix.